The Role of Sharia-Compliant KUR Super Micro Financing in Enhancing MSME Income and Business Development: A Case Study from Bank Syariah Indonesia - Radlyah Hasan Jan; Miranda Suhardi Usman; Fitria Ayu Lestari Niu; Frandy Efraim Fritz Karundeng (International Journal of Islamic Business and Economics (IJIBEC), 2025)
This study aims to evaluate the impact of the KUR Super Micro program on the income of MSEMs financed by Bank Syariah Indonesia Mantos Branch, with a focus on financial inclusion through Sharia-compliant models. It employs a qualitative case study approach, involving detailed interviews with five MSME entrepreneurs and BSI financing officers, direct observations, and document reviews. The findings reveal that before financing, most MSMEs earn IDR 2-3 million monthly; the income increases to IDR 3-6 million after receiving KUR Super Micro Funding. This rise is linked to better inventory management, upgraded equipment, and operational efficiency. All informants repay financing comfortably, with business growth leading to job creation and improved customer satisfaction. The results highlight the KUR Super Micro as a vital tool for empowering MSMEs economically and socially while endorsing Sharia-compliant financial inclusion, suggesting policymakers should continue and expand such financing programs to stimulate entrepreneurship and economic development.